2000
DOI: 10.2460/ajvr.2000.61.1375
|View full text |Cite
|
Sign up to set email alerts
|

Results of a longitudinal study of the prevalence of Escherichia coli O157:H7 on cow-calf farms

Abstract: Implementing control strategies for E coli O157:H7 at all levels of the cattle industry will decrease the risk of this organism entering the human food chain. Devising effective on-farm strategies to control E coli O157:H7 in cow-calf herds will require an understanding of the epidemiologic characteristics of this pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 27 publications
9
54
0
Order By: Relevance
“…Outside Thailand the LTIIa toxin gene has not been reported in hosts other than cattle (33 In this study the simultaneous prevalence of the three traits associated with the O157 genotype is 1:182 E. coli (0.55% of E. coli), similar to reports in the literature (38,47). Our study examined occurrence among total E. coli while most examined occurrence in fecal samples.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Outside Thailand the LTIIa toxin gene has not been reported in hosts other than cattle (33 In this study the simultaneous prevalence of the three traits associated with the O157 genotype is 1:182 E. coli (0.55% of E. coli), similar to reports in the literature (38,47). Our study examined occurrence among total E. coli while most examined occurrence in fecal samples.…”
Section: Discussionsupporting
confidence: 75%
“…Our study examined occurrence among total E. coli while most examined occurrence in fecal samples. The rate of infection in cows is estimated to be 1 to 2 percent (38) and is hence difficult to detect on a farm through single-isolate screening of fecal samples. Our data suggest that screening large numbers of isolates provides an easy approach for detecting this genotype in farm waste ponds.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal shedding of O157 in cattle is reported to be highly intermittent, with variable number of animals in a given herd shedding detectable levels of O157 for several weeks (21,45). These reports support our findings that the fecal shedding profile of O157 in calves inoculated with the wild-type or hha mutant strain continued to show a negative trend for 2 weeks before establishing a low-level intermittent shedding response over the course of the following 2 weeks.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of EHEC O157 in cattle has been reported to be 0.2-60.4% in the United States [10,13,23,28], 1.9% in Australia [7], and 4.2-66.7% in Europe [5,6,16,24]. In Japan, it was reported that the isolation rate of the EHEC was between 0.3% [12] and 6.5% [15] in faeces samples from animals delivered to a slaughterhouse.…”
Section: Shiga Toxin (Stx)-producing Escherichia Coli (Stec) Ismentioning
confidence: 99%